Kidney ultrasound biometric data dynamics in women with gestational hypertension - Tatiana Evgenievna Morozova; Natalya Aleksandrovna Konyshko; Elena Olegovna Samokhina; Artem Sergeevich Konyshko (Society of Diabetic Nephropathy Prevention, 2021)
Introduction: The stable level of morbidity in the Russian Federation of pregnant women with gestational arterial hypertension (GAH) and as a consequence of the disability of women of working age and their offspring actualizes the search for early ultrasound markers of kidney damage as a target organ urgent. Objectives: Despite the variety of publications on ultrasound semiotics of the kidneys, there are no specific biometric parameters of the kidneys in pregnant women without somatic pathology, which actualizes this study. Patients and Methods: A comprehensive clinical examination of 183 outpatients and inpatients (mean age 27.9 ± 4.7 years) with gestational hypertension performed. Results: There is a significant increase in the volume of the right kidney, the left kidney shape index, the diameter of the renal calyces and pelvis, the coefficient of asymmetry, the ratio of the diameter of the renal calyces to the volume of the right kidney with an increase in the degree of gestational hypertension. Conclusion: Structural changes of kidneys are interconnected with hemodynamic parameters observed and can be expressed by mathematical model.